Teknologi Informasi dan Komunikasi untuk Pariwisata: Analisa Isi Laman Resmi Pariwisata Provinsi Kepulauan Riau - Budiarjo Budiarjo (Universitas Sebelas Maret, 2017)
The discovery of Information Communication Technology (ICT) has changed the way of human’s life. Application of ICT in the field of tourism has brought a drastic change among tourism businesses, tourists, and government. In marketing the tourist attraction, the present government no longer needs to spend money in organizing exhibitions, but using the website that is much cheaper. Riau Islands Province is the third provincial tourism destination in Indonesia after Bali and Jakarta. This province is using a website entitled Wonderful Kepri, http://Kepri.travel/ as a means of information and marketing of tourism destinations in its region. The purpose of this study is to describe the extent to which an official website benefits to the customers. This study applies content analysis method either on text or images on the website. The result of this study shows the website provides various menus, interesting and informative for travelers or anyone interested to visit the Riau Islands.